From the tower to the pews: A call for academic theology to re-engage with the local context - Womack, Jonathan M. (HTS teologiese studies, 2019)
This article assesses the shortcomings and the disconnectedness of the current academic theological education in South Africa. It offers a brief history to provide a guiding principle for academic theology. It then proceeds to show the current disconnect and challenges between academic theology and the church, with its primary focus on academic theology. Drawing on original research and reflection on these responses, commodification, euro-centricity and rankings are seen as three traps of modern academics. These three areas have distorted the true content of theological reflection. This article thus clearly highlights the current problem and motivates the need for academic theology and the local church to reconnect with each other. With this article focussing on academic institutions, it calls for the academy to change not in nature but in content, and to draw its content for the local context.